Effect of Media-Assisted Recitation Method Question Cards on Writing Skills Grade V Elementary School Student Nonfiction Text - Nursani N; Sulfasyah S; Sitti Aida Azis (Indonesian Journal of Primary Education, 2022)
This study aims to assess the effect of the question-card-assisted recitation method on the non-fiction text writing skills of fifth grade students. It is a quasi-experimental research with a nonequivalent control group design. The population of the study included all fifth-grade elementary schools in Cluster VII, Pallangga District, Gowa, South Sulawesi, which consisted of 4 schools. Two schools in the cluster were selected by purposive sampling. They were Parangabanoa Elementary School, consisting of 21 students, and Cambaya Elementary School, with 20 students. The first was assigned as the experimental class and the latter as the control class. A writing test was used to measure students' non-fiction writing skills. Descriptive analysis results showed that students' non-fiction text writing skills generally fell into a very poor category (80%) before the implementation of the method and moved to a very good category (90%) after the treatment. The hypothesis testing result was of sig 0.039 0.05, indicating that there was an effect of question card-assisted recitation method on the non-fiction writing skills of the fifth grade students in this study.